2004
DOI: 10.1677/joe.0.1820069
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the rapid release of activin A following acute lipopolysaccharide challenge in the ewe

Abstract: A series of experiments were conducted in adult ewes to delineate the release profile of activin A and its relationship to other cytokines following an i.v. injection of the bacterial cell wall component, lipopolysaccharide (LPS). Following this challenge, plasma activin A increased rapidly and appeared to be released in a biphasic manner, slightly preceding the release of tumour necrosis factor-(TNF ) and before elevation of interleukin (IL)-6 and follistatin levels. The concentration of activin A was correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 43 publications
3
57
0
Order By: Relevance
“…In this context, treatment with exogenous FS has confirmed the important requirement of the early release of activin A to regulate IL-1b, TNF-a and IL-6 secretion induced by LPS. 22,[32][33][34] Moreover, recent evidence has shown that macrophages are able to secrete activin A in response to the activation of TLR2, TLR4 and TLR9 (Figure 1 (1), right panel). [35][36][37][38][39] Accordingly, elevated activin A levels have been observed in a mouse model of endotoxemia and in patients with clinical sepsis condition.…”
Section: Monocytesmentioning
confidence: 92%
“…In this context, treatment with exogenous FS has confirmed the important requirement of the early release of activin A to regulate IL-1b, TNF-a and IL-6 secretion induced by LPS. 22,[32][33][34] Moreover, recent evidence has shown that macrophages are able to secrete activin A in response to the activation of TLR2, TLR4 and TLR9 (Figure 1 (1), right panel). [35][36][37][38][39] Accordingly, elevated activin A levels have been observed in a mouse model of endotoxemia and in patients with clinical sepsis condition.…”
Section: Monocytesmentioning
confidence: 92%
“…However, activin A is also a pro-inflammatory factor and increases dramatically in inflammatory situations. Lots of experiments have demonstrated that activin A is involved in the pathogenesis of fibrotic human diseases and induction of extracellular matrix expression in hepatocytes (8)(9)(10). Our previous studies have found that activin A can increase the production of inflammatory mediator, nitric oxide (NO) in mouse peritoneal macrophages (3).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that activin-A is also induced during inflammatory processes and, more specifically, during infections (6)(7)(8). For example, administration of bacterial endotoxin (LPS) in vivo induces a rapid (within 40 min) release of activin-A in the circulation (7).…”
mentioning
confidence: 99%
“…Growing evidence suggests that activin-A is also induced during inflammatory processes and, more specifically, during infections (6)(7)(8). For example, administration of bacterial endotoxin (LPS) in vivo induces a rapid (within 40 min) release of activin-A in the circulation (7). Of note, activin-A expression is observed at an earlier time point as compared with that of tumor necrosis factor (TNF)-α and well ahead the release of IL-6 (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation